(untitled) (Brazilian Journal of Oceanography, 2004)
The vertical mixing between South Atlantic Central Water (SACW) and Coastal Water (CW) was simulated through microcosm experiments using the autochthonous phytoplankton community (fraction < 150 mm), without nutrient enrichments. SACW is cold (T< 18°C) and nutrient rich, while CW is warmer (T>; 20°C) and oligotrophic. The phytoplankton growth potential of SACW, CW and an equivalent mixture of both (SACW+CW) was compared, under 100, 30 and 10% of sunlight, at surface seawater temperature, in winter and summer conditions. Results demonstrate the importance of SACW as a natural eutrophication agent for the mixing layer, allowing the occurrence of new production by nutrient input, and also as a biological seeder through the development of its autochthonous phytoplankton community when it reaches the euphotic zone. The time lag for phytoplankton development during winter was around 4-5 days, against 1-2 days in summer. The hypothesis of physiological differences between surface and bottom phytoplankton populations from a deep (80 m) and thermally homogeneous water column (common winter feature) was also tested through the microcosm experiments. Results obtained clearly demonstrate that bottom water presented higher phytoplankton growth potential than the surface one.